Description Criteria for Eocene Alveolinids: Examples from Inner Western Anatolia. Issue 1 (November 2019) - Bozkurt, Alper; Gormus, Muhittin
Abstract: Anatomical and morphological features which are used to describe alveolinid species, and their changes during Eocene are the subjects of this study. Changes in some of these features in time and place are important when interpreting geological history of the species. Thus, preliminary results of an ongoing research on Eocene of Inner Western Anatolia are exampled herein, and the relationship between the species is tried to be interpreted. Faunal associations and environmental characteristics of the species are mentioned. The obtained data show that the most important criteria for describing of alveolinids are as follows: test shape, index of elongation, flosculinisation, and coiling types throughout ontogeny. In addition, shape and size of septula and chamberlets, axial thickening, shape and size of the protoconch, and the ratio between the thickness of basal layer and the height of chamber are also important to be considered.